The receipt of the rhetorical terms in “The Miraculous Nature of Qur’an’s” book of Al_ Bakillani - Elouanes, Ilyas; Kbaili, Hamid (Journal of Human Sciences, 2021)
The issue of the Quranic miracles is considered as the most reliable guide to Arabic rhetoric, because it has accompanied it for many decades. By undergoing a descriptive/analytic study of Al-Baqillani’s book, entitled “The miraculous nature of the Qur’an”, we attempt to confirm this issue. We will scrutinize the rhetorical terms presented in this seminal book, where the author compared the speech style of Quran with that of the Arabs, as well as its rhetoric compared with the eloquence of the Arabs; this is done for the purpose of showing its distinction from the ordinary speech and revealing its miracles.